Responsibilities of E-Commerce Platforms and Business Actors in Ensuring Data Protection and Consumer Rights in the Digitalization Era - Hassanah, Hetty; Silaban, Tiffani Sari (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Advances in information technology have given rise to digital trading systems, commonly known as e-commerce, which make it easier for people to conduct online transactions. However, this convenience has led to various legal issues that result in legal consequences for all parties, particularly regarding consumer protection and the security of personal data for marketplace users. The objective of this study is to analyze the liability of e-commerce platforms and business operators in ensuring the protection of personal information and consumer rights in buying and selling activities. The method used is normative legal research employing a statutory approach, a conceptual approach, and a comparative approach. The results of the study indicate that platforms have a responsibility to provide a secure, transparent, and trustworthy system for consumers. Although regulations regarding consumer protection and personal information—such as the Consumer Protection Law (UUPK), the Personal Data Protection Law (UU PDP), and the Electronic Information and Transactions Law (UU ITE)—already exist, their implementation still faces various obstacles. Therefore, stricter regulations and the establishment of a more efficient oversight system are necessary to ensure consumer protection and legal certainty in e-commerce in Indonesia.